IMPLEMENTASI STRATEGI PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DAN CONCEPT MAPPING BERBASIS MULTIPLE INTELLIGENCE TERHADAP PRESTASI BELAJAR AKUNTANSI MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI STKIP HAMZANWADI SELONG LOMBOK TIMUR - Zain, Rohaeniah; Martono, Trisno; Sawiji, Hery (Jurnal Pendidikan Insan Mandiri, 2015)
This research aimed to find out: (1) differences in learning achievement of accounting student who use the Contextual Teaching and Learning and Concept Mapping instructional strategy, (2) differences in learning achievement of accounting student who had high category and low category of multiple intelligence, (3) interaction effect between kategory miltiple intelligence, CTL and Concept Mapping.This study was a experiment. The research was desained by Simple Randomized Subyect Design faktorial 2x2. The research population was II grade Economic Education of Stkip Hamzanwadi. The sample was taken by using nonprobability sampling kuota, obtained 39 students as an CTL class and 38 other in same grade as Concept Mapping class. The data collection was taken by document, questionnaire and test method. Document method was used for finding the Authentic Assesment and the UAS score Basic of Accounting I, as balance test for CTL and Concept Mapping learning. Questionnaire method was used to know the category multiple intelligences of students. Test method was used to know learning achievement of Accounting student.The conclusion of this research were that: (1) There were differences in learning achievement of accounting student who used the Contextual Teaching and Learning and Concept Mapping instructional strategy. (2) There were differences in learning achievement of student who had the high category and the low category of multiple intelligence. (3) There was an interaction effect between kategory miltiple intelligences, Contextual Teaching and Learning and Concept Mapping instructional strategy. The everage learning achievement accounting of CTL class higher than the Concept Mapping class, and different category of multiple intelligences to effect different of learning achievement.Keywords: Multiple Intelligences, CTL, Concept Map, Learning Achievement